A A Reconnoitre Perception of the Muslim Community in Banten Regarding Halal Vaccines After the Covid-19 Pandemic: Reconnoitre Persepsi Komunitas Muslim di Banten Mengenai Vaksin Halal Pasca Pandemi Covid-19 - MuhammadIshom Ishom (Direktorat Jenderal Bimbingan Masyarakat Islam, 2023)
Abstract There have been many changes in the Banten Muslim community in responding to the Covid-19 vaccination, between before and after the pandemic. During the pandemic, many of them refused vaccination for various reasons, including the halal aspect of the vaccine. However, after the end of the pandemic, refusal to vaccinate is no longer heard, especially in the context of vaccination as a prerequisite for Haji and Umrah trips. This study highlights the perceptions of the Muslim community in Banten regarding halal vaccines after the Covid-19 pandemic by using observational data and interviews with prospective Haji and Umrah pilgrims. The choice of this data was based on the prerequisites for a vaccine certificate that they must have before traveling to the holy land. The formulation of the problem is: What causes the decline in the resistance of the Muslim community in Banten to the Covid-19 vaccination, where not all of them have received halal certification? What is their attitude regarding injecting Doses 2 to Booster of the Covid-19 vaccine that has not complied with the MUI fatwa? Using an analytical-descriptive approach, this study concludes that the fading resistance of the Banten Muslim community to the Covid-19 vaccination is related to their needs and the opinion of the Banten religious leaders who allow vaccinations on the grounds of an emergency. Keywords: Banten Religious Leaders, Haji, Umrah, Halal Vaccines, Covid-19